Multimodal Historiography in Spiegelman’s Maus and MetaMaus - Naila Sahar (Linguistics and Literature Review, 2020)
Art Spiegelman’s act of writing (and drawing) Maus is an act of breaking silences. It’s an act of reinterpreting and reconstructing history. By collecting personal memories of his father, Spiegelman recovers, commemorates and recollects the collective heritage of a trauma in a society, where denial and erasure are primary tools of historiography.